Development in regions lagging behind – the case of coal and post-coal regions - Drobniak, Adam (Rozwój w regionach zapóźnionych – przykład regionów węglowych i powęglowych, 2020)
The main topic of the paper refers to the issues of economic transition in regions. The research question is to determine the nature of current development processes in regions lagging behind, in coal regions in particular. The main goal of the article is to present selected modern concepts indicating the paths of the effective reorientation of development processes of such regions, along with their application into the policy framework for the coal regions’ transition. Methodically, the paper is based on a desk research and statistical analysis of time series covering GDP dynamics and job growth for NUTS3 regions in the European Union (EU). The main findings of the research indicate the significant scale of the economic challenges of coal regions in terms of their low productivity measured by the trade-off between the growth of GDP and the increase in the number of jobs, as well as the need to define a complex policy framework which ‘mixes’ a sectoral and territorial approach to achieve an effective coal regions’ transition
Biblioteka Regionalisty, 2020, Nr 20, s. 20-37
Keywords: regions lagging behind; coal regions; productivity; regiony zapóźnione; regiony górnicze; produktywność